Refining surgical therapy of liver cancer in cirrhosis: etiology makes the difference - Colombo, Massimo; Lleo, Ana (Translational Gastroenterology and Hepatology, 2018)
As treatment of hepatocellular carcinoma (HCC) has evolved from an empirical approach to remove the visible tumour towards an evidence-based decision making algorithm, liver transplantation (LT) has progressively emerged as the only curative option for accurately selected patients with a small tumor restricted to the liver (1).